2002
DOI: 10.1116/1.1430246
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of H2O with SrTiO3(100) surfaces

Abstract: Interactions of H2O with SrTiO3(100) surfaces were investigated using temperature-programed desorption (TPD) spectroscopy. TPD spectra show that water desorbs below 300 K on stoichiometric TiO2–terminated SrTiO3(100) surfaces. TPD features at 200–300 K are attributed to the nondissociative adsorption of H2O on cation sites while the TPD feature at 160 K is assigned to the desorption of multilayer water. However, TPD spectra for H2O on reduced SrTiO3(100) surfaces exhibit additional desorption features at 300–5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
8
36
0
Order By: Relevance
“…We take this as confirmation that also the gradient-corrected xc functional employed here is able to capture the essential physics -at a (still) significantly lower computational cost that in turn enables us to perform calculations in much larger surface unit-cells. The data for these cells also compiled in Table II on the other hand demonstrates that the latter is a crucial point as the binding energy exhibits a strong coverage dependence, reflecting overall repulsive interactions consistent with the TPD data from Wang et al 3 . A value fairly representing the low-coverage limit is only reached in (2 × 2) cells, and as we will discuss in Section III.C below, it is this limit that is the appropriate one to discuss the Iwahori FFM experiments 6 .…”
Section: A Sro-terminationsupporting
confidence: 80%
See 1 more Smart Citation
“…We take this as confirmation that also the gradient-corrected xc functional employed here is able to capture the essential physics -at a (still) significantly lower computational cost that in turn enables us to perform calculations in much larger surface unit-cells. The data for these cells also compiled in Table II on the other hand demonstrates that the latter is a crucial point as the binding energy exhibits a strong coverage dependence, reflecting overall repulsive interactions consistent with the TPD data from Wang et al 3 . A value fairly representing the low-coverage limit is only reached in (2 × 2) cells, and as we will discuss in Section III.C below, it is this limit that is the appropriate one to discuss the Iwahori FFM experiments 6 .…”
Section: A Sro-terminationsupporting
confidence: 80%
“…in terms of molecularly adsorbed water [2][3][4][5] . Even though an absolute coverage calibration was rarely achieved, it is quite clear that these studies operated mostly in the higher coverage regime.…”
Section: Fig 4: (Color Online)mentioning
confidence: 99%
“…1 Among all surfaces, interaction with metal oxide perovskites is of great interest because its fundamental aspects are still not well understood and it has implications in many processes, from ferroelectric polarization screening phenomena to surface catalysis and oxides surface chemistry in general, as well as a strong impact in applied electronics and sensing devices. Among the studies devoted to water interaction with perovskite-type oxide surfaces, emphasis has been placed on those exposing a TiO2 terminated surface [2][3][4][5] such as SrTiO3 (STO), [6][7][8][9][10][11][12][13] BaTiO3 (BTO) [14][15][16] or even Pb(Zr0.25Ti0.75)O3 (PZT) 17 due to its proximity with photocatalytic reactions mediated by TiO2. 18 Theoretical studies on water interaction with surfaces can be classified into those addressing ideal surfaces for a fundamental point of view and those which study reconstructed surfaces, closer to what can be expect for coarse materials exposed to ambient.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52][53][54][55][56] Our previous studies on angle-resolved X-ray photoelectron spectroscopy (ARXPS) 5,7) concur with such a view. Wang et al 54) observed that water molecules adsorb, even at 177 C, onto defective TiO 2 -terminated SrTiO 3 (001) single crystal surfaces prepared by 2 kV argon-ion bombardment for 15 min; however, they observed that water adsorption at room temperature becomes negligible after annealing in vacuum at 377 C. Eriksen et al 55) prepared oxygendeficient SrTiO 3 single-crystal surfaces, with roughly one oxygen atom missing from every two units, by 1 kV argonion bombardment at approximately 5 AÁcm À2 for 10 min. Note that the surfaces of our specimens are not treated by argon-ion bombardment, and that SrO surface segregation is not sensitive to oxygen, 2,5,7) and that SrO, which tends to form Sr(OH) 2 or SrCO 3 after exposure to air, tends to segregate near steps.…”
Section: Methodsmentioning
confidence: 60%